The relationship between oil prices and energy sector stocks in the global recession issue - Christina Mikhaila Suoth; Feibe Cindy T Rumengan (Yayasan Widyantara Nawasena Raharja, 2023)
Changes in world oil prices as a result of global issues have had a certain impact on the capital market in Indonesia. This study aims to examine the relationship between stock prices in the energy sector and fluctuations in world oil prices. Observations were made from January to April 2023 with a sample of 76 firms in the energy sector. The result of the analysis shows that stock prices in the energy sector have high variability throughout the observation period. In addition, this study finds that energy sector stock prices have a positive relationship with world oil prices.